Precalving Distribution and Abundance of Barren-Ground Caribou on the Northeastern Mainland of the Northwest Territories - Heard, D.C.; Williams, T.M.; Jingfors, K. (ARCTIC, 1986)
An aerial survey with about 5% coverage of the northeastern mainland, Northwest Territories (342,000 sq. km.) was conducted 5-10 May 1983. We estimated there were 120,000 ± 13,900 caribou (0.35 ± 0.041 caribou/sq km) in the study area. Mean caribou group size ranged from 6 to 11 among nine strata and was correlated (r = 0.81) with stratum caribou density. We found four regions of high caribou density. Three regions coincided with the calving grounds of previously defined herds, the Melville, Wager, and Lorillard, and the fourth suggests a discrete population in the previously unsurveyed area south of the Queen Maud Gulf.Key words: caribou, aerial survey, Rangifer, distribution, abundance, northeastern Northwest Territories Mots clés: caribou, inventaire aérien, Rangifer, distribution, abondance, nord-est des Territoires du Nord-Ouest